2005
DOI: 10.1002/cyto.a.20187
|View full text |Cite
|
Sign up to set email alerts
|

DNA transitions induced by binding of PARP‐1 to cruciform structures in supercoiled plasmids

Abstract: Background: Poly(ADP-ribose)polymerase-1 (PARP-1) binds to single and double-stranded breaks in DNA, but less well known is its affinity for undamaged DNA. Previously, we have shown that PARP-1 also binds to the hairpin structures in DNA models. The mechanism underlying these interactions remains to be defined. Methods: We analyzed atomic force microscopy (AFM) images of complex of PARP-1 proteins with supercoiled plasmids containing cruciform structures. Using volume measurement analysis of molecules of PARP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…It occurs by heteromodification of histones, which promotes the decondensation of high order chromatin, and by binding to enhancer/promoter regulatory cis-elements (44). Previous studies have reported that PARP-1 recognizes unusual DNA conformations such as hairpins/cruciforms (47)(48)(49) and the G-quadruplex formed by a cis-element in the human KRAS promoter (8). Interestingly, Ladame and co-workers (50) have shown that PARP-1 undergoes automodification after binding to the c-kit quadruplex.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs by heteromodification of histones, which promotes the decondensation of high order chromatin, and by binding to enhancer/promoter regulatory cis-elements (44). Previous studies have reported that PARP-1 recognizes unusual DNA conformations such as hairpins/cruciforms (47)(48)(49) and the G-quadruplex formed by a cis-element in the human KRAS promoter (8). Interestingly, Ladame and co-workers (50) have shown that PARP-1 undergoes automodification after binding to the c-kit quadruplex.…”
Section: Discussionmentioning
confidence: 99%
“…Binding reactions were carried out with 0.1 M 497L RNA and 0.5 M HDAg-160 for 5 min at 37°C in 80 mM NaCl, 10 mM Tris, pH 7.5. Freshly cleaved muscovite mica was incubated in a mixture of a 1-(3-aminopropyl)silatrane (APS) solution for 30 min to prepare APS-mica as described previously (34). Sample droplets (5 l) were deposited on APS-mica for 2 min and then washed with deionized water and dried with nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…PARP-1 activity is also linked to coordination of chromatin structure and gene expression [103]. It was reported that PARP-1 can bind to DNA hairpins and promoter region in superhelical DNA and promote formation of cruciform structure [104]. PARP-1 recognizes distortions in the DNA backbone allowing it to interact with three- and four-way junctions [105].…”
Section: Proteins Involved In Interactions With Quadruplex Dnamentioning
confidence: 99%
“…Pull-down and chromatin immunoprecipitation assays revealed that this quadruplex-forming element is bound by MAZ and PARP-1 proteins [62]. It was also found that using plasmid DNA targets, binding of PARP-1 to DNA can induce changes in DNA topology [104]. Furthermore, a critical quadruplex-forming element of murine KRAS oncogene interacts with MAZ and PARP-1 proteins via conformational changes from duplex to quadruplex DNA.…”
Section: Proteins Involved In Interactions With Quadruplex Dnamentioning
confidence: 99%